2021
DOI: 10.1007/s11097-021-09755-w
|View full text |Cite
|
Sign up to set email alerts
|

Pretend play with objects: an ecological approach

Abstract: The ecological approach to object pretend play, developed from the ecological perspective, suggests an action-and affordance based perspective to account for pretend object play. Theoretical, as well as empirical reasons, support the view that children in pretense incorporate objects into their play in a resourceful and functionally appropriate way based on the perception of affordances. Therefore, in pretense children are not distorting reality but rather, they are perceiving and acting upon action possibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…The next step is to re-articulate this new perspective in practice. This means exploring the connection between ecological psychology and enactivism, and STS, where ecological psychology and enactivism could focus on the experiential and normative aspects of coordination among different practices, as already happens in the context of other kinds of practices, such as architecture (Rietveld and Kiverstein, 2014;Rietveld and Brouwers, 2017;van Dijk andRietveld, 2017, 2021), pretend play (Szokolszky and Read, 2021;Murphy, 2022), education (Young, 2004;Gresalfi et al, 2012;Phillips and Finn, 2022), and many others. On the contrary, STS could provide the methods for studying the practices themselves, e.g., through ethnography and qualitative research (Latour and Woolgar, 1979;Latour, 1987;Mol, 2002;Greiffenhagen et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The next step is to re-articulate this new perspective in practice. This means exploring the connection between ecological psychology and enactivism, and STS, where ecological psychology and enactivism could focus on the experiential and normative aspects of coordination among different practices, as already happens in the context of other kinds of practices, such as architecture (Rietveld and Kiverstein, 2014;Rietveld and Brouwers, 2017;van Dijk andRietveld, 2017, 2021), pretend play (Szokolszky and Read, 2021;Murphy, 2022), education (Young, 2004;Gresalfi et al, 2012;Phillips and Finn, 2022), and many others. On the contrary, STS could provide the methods for studying the practices themselves, e.g., through ethnography and qualitative research (Latour and Woolgar, 1979;Latour, 1987;Mol, 2002;Greiffenhagen et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that to be used instead of another one, a prop in pretend play should afford the same action or gesture as a missing object 11 (El'konin, 1978;Vygotsky, 1983; see also Landau et al, 1988;Smith, 2005). Hence, in pretend play involving object substitution, a child has to first perceive a particular affordance of the prop (Dent-Read, 1997;Szokolszky and Read, 2021).…”
Section: Pretend Play and The Creation Of New Affordancesmentioning
confidence: 99%